Evaluation of an edible coating based whey protein and beeswax on the physical and chemical quality of gooseberry (Physalis peruviana L.) - Oswaldo Osorio Mora; David Fernando López Enriquez; Liseth Yurani Cuatin Ruano; Johana Carolina Andrade (Acta Agronómica)
It was developed and optimized an edible coating based whey protein concentrate and beeswax. An experimental design 32 was used, this was evaluated by response surface methodology, it was obtained that the optimal formulation with a concentration of 15% beeswax and 10% whey protein, reduced by 35.49% weight loss of the fruit with respect to weight loss of control treatments. The optimal treatment was characterized and evaluated on the physicochemical properties of the gooseberry (Physalis peruviana L.) in two storage conditions: environment (17- 2 ºC y HR: 69%) and cooling (4 -2 ºC y HR: 66%). The results for the 15th day evaluation indicated a decrease in the percentage of weight loss, in storage environment and cooling (36.20% and 41.50% respectively). Control treatments decreased acidity in storage environment and cooling 3.88% and 4.92% respectively, compared to coating treatments. pH have not significantly change with any treatment. The coating prevent reduction of soluble solids 3.76% to environmental conditions and 2.27% to cooling conditions. For maturity index were not any significant changes between control treatments and coating treatments, in both conditions. The firmness remained without any significant changes except treatment environment uncoated, this presented a loss of firmness of 12.04% compared to the treatment environment coated. The respiration rate indicates a climacteric peak at day 8th for environment and at day 10th for cooling. For some properties, the cooling treatment uncoated and environment treatment coated have not any significant changes whereby the coating application can be an alternative to the cooling.